PERCEPCIONES AMBIENTALES DEL COMERCIO DEL ZOOTERÁPICOS POR HERBOLARIOS EN EL NORDESTE DE BRASIL (Biocenosis, 2015)
This is the first study that investigated the perceptions of herbalists in public markets in the city of Juazeiro do Norte, Brazil. Through the results we analyze the socio-environmental context they are embedded. We have seen that despite the conservation policies, this practice still remains from one generation to another.
Keywords: Traditional knowledge; Caatinga biome; Ethnoecology; Conservation